The Analysis Of Factors Influencing Profitability In Islamic Commercial Bank - Adhia Apriyani (UIN Mataram, 2020)
This research aims to examine the picture and analyze the factors which influence the profitability in Islamic Commercial Bank (BUS – Bank Umum Syariah) in the period. The profitability growth in the last five years has tended to decrease. This is caused by the decrease in net income being greater than the decrease in total assets. The research method used is the descriptive and verificative method. The population for the data collection is the Islamic Commercial Bank. The method used for sampling in this study is purposive sampling with a total sample of 12 Islamic Commercial Bank companies in five years with 60 of observation data. The data used is secondary data. The statistical analysis technique used in this study is panel data regression. The dependent variable in this study is profitability and the independent variables in this study are the risk of problematic financing, profit sharing financing, capital adequacy, and operational cost efficiency. The results shows that the risk of problematic financing, profit sharing financing, capital adequacy, and operational cost efficiency has an effect significant on profitability. Partially that profit sharing financing and capital adequacy in positive has an effect significant on profitability, while the risk of problematic financing and operational cost efficiency in negative has an effect an significant on profitability.